Mental health and sleep quality: are intuitive eating, hedonic hunger and diet quality, determinants? a cross-sectional study - Ateş, Kevser Sare; Bakırhan, Hande; Kalkan, Indrani (My University, 2024)
Background Intuitive eating may predict better psychological and behavioral health. Intuitive eating, hedonic hunger, and diet quality may affect individuals’ mental health and sleep quality. Methods Descriptive cross-sectional study developed with an online questionnaire for randomly selected volunteers (n=351) aged 19-64 years. Hedonic hunger status was evaluated by Power of Food Scale (PFS), intuitive eating by Intuitive Eating Scale-2 (IES-2), mental health status by Warwick-Edinburgh Mental Well-Being Scale (WEMWBS) and sleep quality by Pittsburgh Sleep Quality Index (PSQI). Food consumption records were taken to evaluate individuals’ dietary quality, using Healthy Eating Index (HEI)-2015. Results It was found that 50.7% of the participants exhibited intuitive eating behavior, while 65.0% experienced hedonic hunger. When the diet quality was examined, it was found that 65.2% of the participants had poor diet quality, while 33.6% needed to improve their diet quality. Sleep quality and mental health status of individuals exhibiting intuitive eating behavior were significantly better (p<0.05). Diet quality was not associated with mental health, intuitive eating, hedonic hunger and sleep quality scores (p>0.05). While there was a weak negative correlation between intuitive eating and PSQI score (r=-0.160, p<0.05), while a positive correlation was found between hedonic hunger and PSQI score (r=0.286, p<0.05). Intuitive eating was associated with better sleep quality, as lower PSQI scores indicate better sleep quality. Intuitive eating was also associated with better mental health (r=0.339, p<0.05). Conclusion This study reveals that intuitive eating behavior is associated with better sleep quality and mental health, while hedonic hunger behavior is associated with poor sleep quality.
Keywords: Diet Quality; Hedonic Hunger; Intuitive Eating; Mental Health; Sleep Quality